Three-dimensional carbon nanosheets derived from micro-morphologically regulated biomass for ultrahigh-performance supercapacitors. (November 2019) - Liu, Mingren; Zhang, Kejing; Si, Mengying; Wang, Haiying; Chai, Liyuan; Shi, Yan
Abstract: The exploration of diverse plant precursors has attracted intense attention in the development of advanced carbon materials for supercapacitors. However, tailoring the natural nanoarchitectures at plant-cell-wall level remains challenged. Herein, the micromorphological regulation of woody precursors for 3D scaffolding framework of 2D porous carbon nanosheets is demonstrated by sequential alkaline oxidation, bio-swelling and low-temperature carbonization. By featuring an outstanding N-doping level (8.7 at%), O-doping level (20.9 at%), rational hierarchical porosity and strengthened mechanical stability, the resulting carbon exhibits ultra-high gravimetric capacitances of 508 F g −1 and 360 F g −1 at 1.0 A g −1 in the three- and two-electrode system of 6 M KOH electrolyte, respectively. Moreover, an impressive rate capability (394 F g −1 at 50 A g −1 ) and long-cycling stability (95% after 12, 000 cycles) have also been obtained. The fabricated symmetric supercapacitor in ionic liquid electrolyte further displays outstanding synergetic energy-power output properties (94.2 W h kg −1 at 0.5 kW kg −1 and 45.7 W h kg −1 at 21.1 kW kg −1 ). Stemming from the distorted layer structure of delignified and swelled cell walls, this strategy enables the penetration of chemical reagents into highly crystalline cellulose microfibrils. The scalable route to produce high-performance carbons from diverse plant candidates is thus extended. Graphical abstract: Image 1